SOROLOGICAL STUDY OF COINFECTION LEISHMANIA INFANTUM E MYCOBACTERIUM LEPRAE IN AREA OF ENDEMICITY HIGH - Carneiro, Isabel Paiva Dias Mendes (2015)
Introduction: The Northeast region accounts for 55% of leprosy cases and nearly 50% of cases of visceral leishmaniasis in Brazil. Ceará, in particular the Fortaleza capital is responsible for a large number of new cases of these diseases. This fact is reinforced by the correlation in the distribution of cases of these diseases in the state of Ceará counties where according to the data of the State Health Departament (2013), we observed strong epidemiological correlation between cases of leprosy and visceral leishmaniasis in 184 counties mostly in Fortaleza. Objectives: Our objective was to analyze the production of anti-PGL1 IgM antibodies in patients with visceral leishmaniasis untreated. Materials and Methods: 28 patients with clinical and laboratory confirmation for visceral leishmaniasis followed at São José Hospital for Infectious Diseases. Results: As to gender, 21 were males and 7 females, with a median age of 20,5 years (var 3-76 years.), Of which 15 patients did not require hospitalization and 13 were hospitalized for an average 28 days (var. 5 to 28 days). The mean and standard deviation of the anti-IgM PGL1 index was 1.91 ± 0.69, and 78.6% considered seropositive. Conclusion: It was not observed any difference between gender, age, necessity or not hospitalization, or time treatment. The high frequency of positive IgM anti-PGL1,can be secondary to polyclonal activation occurring in kala-azar, hindering the possibility of detection of M. leprae infection by serologic evaluation in high endemicity area for visceral leishmaniasis.